2017
DOI: 10.14744/anatoljcardiol.2017.7831
|View full text |Cite
|
Sign up to set email alerts
|

Role of sympathetic cotransmitter galanin on autonomic balance in heart failure: an active player or a bystander?

Abstract: Objective:Galanin, a cotransmitter similar to neuropeptide Y (NPY), aggravates autonomic imbalance in systolic heart failure (HF) by attenuating vagal tonus after burst sympathetic activity. In animal HF models, galanin antagonists have improved cardiac function. To determine whether galanin is a promising therapeutic target in HF, we studied its concentrations in HF patients and evaluated its correlation with NPY, markers of humoral activity such as pro-BNP and copeptin, and echocardiographic parameters of HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…In two studies which measured NPY levels in heart failure patients post-exercise, one found no significant increase, whilst one found an increase from 50+/−5 to 60+/−6 pmol/l (Maisel et al, 1989 ; Ullman et al, 1994a ). A more recent study has also confirmed higher NPY levels in heart failure patients, which correlated with BNP levels and echocardiographic markers of heart failure severity (Ozkaramanli Gur et al, 2017 ).…”
Section: Neuropeptide Y As An Important Mediator Of Cardiovascular DImentioning
confidence: 76%
“…In two studies which measured NPY levels in heart failure patients post-exercise, one found no significant increase, whilst one found an increase from 50+/−5 to 60+/−6 pmol/l (Maisel et al, 1989 ; Ullman et al, 1994a ). A more recent study has also confirmed higher NPY levels in heart failure patients, which correlated with BNP levels and echocardiographic markers of heart failure severity (Ozkaramanli Gur et al, 2017 ).…”
Section: Neuropeptide Y As An Important Mediator Of Cardiovascular DImentioning
confidence: 76%
“…A recent prospective case-control study in the clinical realm showed that unlike pro-BNP, copeptin and NPY, galanin levels were similar among patients with HF patients and control subjects while pro-BNP was the only significant determinant of galanin levels in HF patients[ 236 ]. Authors postulated that galanin most likely has a predominant paracrine modulatory function at the level of peripheral cardiac sympathetic nerves, therefore, its circulating levels in plasma might not reflect the degree of its local involvement in sympathovagal crosstalk.…”
Section: Laboratory Biomarkers Of Sympathetic Nervous System Activatimentioning
confidence: 99%
“…In this study, we asked if NPY has an effect on DOXinduced cardiotoxicity. Previous studies have shown a diverse role for NPY in different types of cardiomyopathies, including an increase in NPY levels and effects on several pathological processes involved also in DOX-induced cardiotoxicity [11,30,[53][54][55][56]. Transgenic NPY overexpression had some effects on DOX-induced toxicity.…”
Section: Discussionmentioning
confidence: 91%